UNVEILING DUALITIES: US RHETORIC AND REALITY IN GLOBAL NUCLEAR NON-PROLIFERATION UNDER TRUMP AND BIDEN ADMINISTRATIONS (Margalla Papers, 2023)
The image the United States has always projected of itself in the international community is that of a state that is nuclear responsible and bears the responsibility to keep nuclear proliferation in check. To this effect, it uses sanctions, international pressure, and harsh language with states it deems to be in violation of the obligations of the global nuclear non-proliferation regime. On the other hand, however, there is doubt about the United States' own dedication to the cause of nuclear non-proliferation. This paper is an attempt to examine the role the US has played vis-à-vis nuclear proliferation. It deals with the question: what role US has played in promoting nuclear non-proliferation and what its probable effects are on the international nuclear non-proliferation landscape. It argues that the US has not only engaged in excessive nuclear proliferation since 1945 but has also damaged the international nuclear non-proliferation regime, thereby reduced restraints, and set dangerous precedence for other states. The paper recommends that US may lead the world towards nuclear non-proliferation and disarmament by example rather than unfair coercion. Bibliography EntryRashid, Asma and Aiman Saif Ullah. 2023. "Unveiling Dualities: US Rhetoric and Realty in Global Nuclear Non-Proliferation under Trump and Biden Administrations." Margalla Papers 27 (2): 60-70.